Undergraduate degrees that train students for soil science careers at universities in the USA and its territories. Issue 6 (21st December 2020) - Brevik, Eric C.; Dolliver, Holly; Edinger‐Marshall, Susan; Itkin, Danny; Johnson‐Maynard, Jodi; Liles, Garrett; Mbila, Monday; Moorberg, Colby; Sanchez‐de Leon, Yaniria; Steffan, Joshua J.; Ulery, April; Vaughan, Karen
Abstract: Several soil science education studies over the last 15 yr have focused on the number of students enrolled in soil science programs. However, no studies have quantitatively addressed the number of undergraduate soil science preparatory programs that exist in the United States, which means we do not have solid data concerning whether overall program numbers are declining, rising, or holding steady. This also means we do not have complete data on the same trends for total undergraduate soil science students in the United States. This study used the US Office of Personnel Management (OPM) Soil Science Series 0470 standards to determine if a bachelor's degree met soil science preparatory criteria. Lists of the approximately 3, 500 regionally accredited colleges and universities were obtained from the regional accrediting agencies; the website of each of the colleges and universities was visited to determine if they had a degree program that met the OPM 0470 criteria. Ninety‐two soil science preparatory degree programs were identified at 86 colleges and universities. These programs were primarily linked to (a) agriculture, (b) environmental science, and (c) soil and water science, based on the number of degree occurrences. This study creates a baseline for future studies that can investigate trends in soil science programs. It also provides an insight into the institutions and degree programs that should be included in soil science education studies.